L-Carnitine supplementation improved population growth, photosynthetic pigment synthesis and antioxidant activity of marine Chlorella sp. - Sen Wang; Yu-ke Chen; Abdallah Ghonimy; Ting Yu; Yong-sheng Gao; Zhen-chao Wu; Qiu-ju Wang; Dong-ming Zhang (Aquaculture Reports, 2020)
High nutritive microalgae is a key factor that affecting the live feeds nutritional value and subsequently fish fry quality. We evaluated the effect of l-carnitine supplementation level on the population growth, photosynthetic pigment biosynthesis, and antioxidant capability of the pigment-protein complexes in the marine Chlorella sp. Five different l-carnitine levels (0, 5, 50, 100, and 200 mg L−1) were supplemented in the microalgae media for 10 days. The results demonstrated that l-carnitine increased the population density and specific growth rate in LC 5 (P < 0.05). While the β-carotene and iron contents were elevated in LC 5 and LC 50 (P < 0.05). Apart from, chlorophyll a, chlorophyll b, and magnesium contents were higher in the LC 5 (P < 0.05). While LC 5 had higher metal chelation in pigment-protein complexes (P < 0.05). Meanwhile, psy and chld gene expressions were up-regulated in the LC 5 and LC 50 (P < 0.05). Taken together, LC 5 and LC 50 could improve the population growth, pigment synthesis, antioxidant capacity and up-regulate the relative expression levels of photosynthetic pigment synthesis genes in marine Chlorella sp. Therefore, l-carnitine has comprehensive effects on algae production.